The Influence of Primitive Subgroups on the Structure of Finite Groups (Communications in Mathematical Research, 2021)
A subgroup $H$ of a group $G$ is said to be primitive if it is a proper subgroupof the intersection of all subgroups of $G$ containing $H$ as its proper subgroup. Thepurpose of this note is to go further into the influence of primitive subgroups on thestructure of finite groups. Some new results are obtained.
Keywords: primitive subgroup; supersoluble group; structure of group.